Downward nominal wage rigidity in Canada: Evidence against a "greasing effect". (31st July 2018) - Wagner, Joel
Abstract: The existence of downward nominal wage rigidity (DNWR) has often been used to justify a positive inflation target. It is traditionally assumed that positive inflation could "grease the wheels" of the labour market by putting downward pressure on real wages, easing labour market adjustments during a recession. A rise in the inflation target would attenuate the long‐run level of unemployment and hasten economic recovery after an adverse shock. Following Daly and Hobijn (2014), we re‐examine these issues in a model that accounts for precautionary motives in wage‐setting behaviour. We confirm that DNWR generates a long‐run negative relationship between inflation and unemployment, in line with previous contributions to the literature. However, we also find that the increase in the number of people bound by DNWR following a negative demand shock rises with the inflation target, offsetting the beneficial effects a higher inflation target has on closing the unemployment gap. As an implication, contrary to previous contributions that neglected precautionary behaviour, the speed at which unemployment returns back to pre‐crisis levels during recessions is relatively unaffected by variations in the inflation target. Résumé: Rigidité à la baisse des salaires nominaux au Canada: résultats remettant en question l'effet de lubrification . L'existence de la rigidité à la baisse des salaires nominaux (RBSN) a souvent été utilisée pour justifier une cible d'inflation positive. Traditionnellement on présume qu'une inflation positive peut "lubrifier les rouages" du marché du travail en mettant une pression à la baisse sur les salaires réels, facilitant ainsi les ajustements dans le marché du travail au cours d'une récession. Un accroissement dans la cible d'inflation atténuerait l'effet à long terme sur le niveau de chômage et pourrait accélérer la reprise après un choc adverse. À la suite de Daly et Hobijn (2014), l'auteur réexamine ces questions dans un modèle qui tient compte du motif de précaution dans le comportement de détermination des salaires. On confirme que la RBSN génère une relation négative à long terme entre inflation et chômage, résultat déjà inscrit dans la littérature spécialisée. Cependant on découvre aussi que le nombre de personnes frappées par la RBSN à la suite d'un choc négatif dans la demande augmente à proportion que la cible d'inflation augmente, compensant les effets bénéfiques d'une cible d'inflation accrue sur l'écart de chômage. Voilà qui implique que, contrairement à ce qui est rapporté dans une littérature qui négligeait le comportement de précaution, la vitesse avec laquelle le chômage retourne à son niveau de l'avant‐crise est relativement non‐affectée par les variations dans la cible d'inflation.